Vibrace při frézování kovů - Dvořák, Jan (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2016)
Tato práce obsahuje teoretický popis frézování, matematický popis kmitání a příčiny vzniku samobuzeného kmitání při frézování. Dále se zabývá dynamickým měřením obráběcích strojů a diagramem stability. V poslední řadě uvádí způsoby předcházení, odstranění nebo maximální redukci samobuzeného kmitání při frézování.

This thesis contains theoretical description of milling, mathematical description of oscillation and causes of self-excited vibrations during the milling process. It further contains dynamic measurement of machine-tools and stability lobe diagram. At last it states different ways of prevention, removal or maximum reduction of self-excited vibrations during the milling process.
Vibration at milling of metal
Keywords: Frézování; regenerativní kmitání; diagram stability; tlumení vibrací; Milling; regenerative chatter; stability lobe diagram; damping of chatter